A Novel Homozygous Missense Mutation in the Zinc Finger DNA Binding Domain of GLI1 Causes Recessive Post-Axial Polydactyly - Umair, Muhammad; Ahmad, Farooq; Ahmad, Saeed; Alam, Qamre; Rehan, Mohd; Alqosaibi, Amany I.; Alnamshan, Mashael M.; Rafeeq, Misbahuddin M; Haque, Shahnaz; Sain, Ziaullah M; Ismail, Muhammad; Alfadhel, Majid (Frontiers in Genetics, 2021)
Background: Polydactyly is a prevalent digit abnormality characterized by having extra digits/toes. Mutations in eleven known genes have been associated to cause nonsyndromic polydactyly: GLI3, GLI1, ZRS regulating LMBR1, IQCE, ZNF141, PITX1, MIPOL1, FAM92A, STKLD1, KIAA0825, and DACH1. Method: A single affected family member (IV-4) was subjected to whole-exome sequencing (WES) to identify the causal gene. Bi-directional Sanger sequencing was performed to segregate the identified variant within the family. In silico analysis was performed to investigate the effect of the variant on DNA binding properties. Results: whole-exome sequencing identified a bi-allelic missense variant (c.1010C > T; p. Ser337Leu) in exon nine of GLI1 gene located on chromosome 12q13.3. With the use of Sanger sequencing, the identified variant segregated perfectly with the disease phenotype. Furthermore, in silico analysis of this DNA binding protein revealed that the variant weakened the DNA binding interaction, resulting in indecorous GLI1 function. Conclusion: Herein, we report a novel variant in GLI1 gene, causing autosomal recessive post-axial polydactyly type A (PAPA) type 8. This confirms the critical role of GLI1 in digit development and might help in genotype–phenotype correlation in the future.